Transitional Care in Later Life: Improve the Move. - Chalmers, Sandra A.; Coleman, Eric A. (Generations)
Part of a special issue on chronic conditions in later life. Researchers at the University of Colorado Health Sciences Center (UCHSC) Care Transitions Program are examining interventions designed to manage the vulnerabilities experienced by parents during transitional care and are developing new approaches for enhancing outcomes for patients during transfers. During transfers, patients can be exposed to medication errors, duplication of services, and unnecessary use of high-intensity care settings. According to the UCHSC program, improving transitional care will demand intervention at the level of patient, practitioner, delivery system and policy maker.